The secret life of the brain : Unlocking the mysteries of the mind - David, Alfred (Cassell, 2019)
"In the long history of the study of anatomy, neuroscience is a relatively new field and there are plenty of mysteries yet to be uncovered. The Secret Life of the Brain explores the fascinating advances that have been made in the field so far, from the intricacies of memory and intelligence, to the enigmatic workings behind our sense of humour and our dreams."--